A NOVA CONDIÇÃO URBANA: SOBRE A VIDA NA CIDADE NA “ERA DO HOMEM ENDIVIDADO” - Soares Pereira, Cláudio Smalley (2020)
Abstract: This article analyses the process of urbanization and the urban space production in the contemporary period. We have raise the hypothesis that the present historical period is marked by rapid urbanization process on a global scale, which also presents some particular characteristics. It focuses on the problematization of the links between urbanization, dynamics of financialization and consumption along with an increasingly widening gap of a poorer and more selective, individualistic, segmented urban experience. In other words, on one hand, we note a rapprochement between the urbanization dynamics and the production of cities while, on the contrary, there is the logic of financial systems in the making of the indebted man, which, in turn, results in urban experiences that progressively deny a constitutive entanglement of the very idea of a city. Keywords: city, urban condition, urban experience, indebtedness